3(2y-1)-2(1-y)=0
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 19:34:14
3(2y-1)-2(1-y)=03(2y-1)-2(1-y)=03(2y-1)-2(1-y)=0解3(2y-1)-2(1-y)=06y-3-2+2y=08y=5y=5/83(2y-1)-2(1-y)=
3(2y-1)-2(1-y)=0
3(2y-1)-2(1-y)=0
3(2y-1)-2(1-y)=0
解
3(2y-1)-2(1-y)=0
6y-3-2+2y=0
8y=5
y=5/8
3(2y-1)-2(1-y)=0
即
6y-3-2+2y=0
6y+2y-3-2=0
8y=5
y=5/8
8y=5
y=5/8
y(y-2)²-y(y+3)(y-5) y=1/2 化简求值
y(y-2)²-y(y+3)(y-5) y=1/2 化简求值
y(y-2)²-y(y+3)(y-5) y=1/2 化简求值
常微分方程的通解dy/dx=(x-y+1)/(x+y-3)y^4=2y^n+y=0y''+6y'+9y=e^(-3x)y''+y'-2y=4e^(2x)
方程y''-4y'+13y=0的通解方程y''=(1+y'*y')/2y的通解
y (3y^2+8y-3)-6y(3y+2y-1)+9y
9y^3-9y^2+2y+1=0 求3y-1=?
微分方程y''=3√y,x=0,y=1,y'=2
4Y^3+3Y^2+4Y+1=0求Y
[T,Y]=ode45(@rigid,[0 1],[rand(15,1)]);plot(T,Y(:,1),'-',T,Y(:,2),'-.',T,Y(:,3),'.',T,Y(:,4),'-',T,Y(:,5),'-.',T,Y(:,6),'.',T,Y(:,7),'-',T,Y(:,8),'-.',T,Y(:,9),'.',T,Y(:,10),'-',T,Y(:,11),'-.',T,Y(:,12),'-.',T,Y(:,13),'.',T,Y(:,14),'-',T,Y(:,15),'.')
y'''-3y''+3y'-y=-1 y''(0)=y'(0)=1 y(0)=2 用laplace变换求解
解方程,3y^3+(y+3)(6-2y)+3y(y+2)(2-y)-2(y^2+1)=0
解方程:3y^2-(2y+1)(y-1)=(y-5)(y+1)
解方程3y^2-(2y+1)(y-2)=(y-5)(y-1)
2(y-4)(3y+2)-5(-3y+7)(y+1),其中y=-1
解方程:3y²-(2y+1)(y-2)=(y-5)(y+1)
(y-4)(3y+2)-(3y-7)(2y+1),其中y=4/3
解分式方程(y+3)/(y^2+y)-1/(1-y)=4/y要过程